2023
DOI: 10.3390/bs13070560
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Frontier and Prospect of Service Robots in the Tourism and Hospitality Industry Based on International Core Journals: A Review

Abstract: This paper used the mixed research method of bibliometric and content analysis to study 284 studies on service robots in the tourism and hospitality industry collected from the Web of Science database. Results show that research in this field started late, and that the COVID-19 pandemic has promoted the rapid growth of the number of research papers. The International Journal of Contemporary Hospitality Management has so far published the most number of papers. Numerous scholars from universities in different r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 89 publications
(167 reference statements)
0
0
0
Order By: Relevance
“…The concept of risk perception has been highly studied in tourism; however, the literature remains fragmented, resulting in a lack of a cohesive and comprehensive framework [1]. Previous studies have found that tourists' risk perception has a high probability of impacting the image of tourist destinations and the intention to visit a destination [36], but little or no evidence is available on the role of religion values or related cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The concept of risk perception has been highly studied in tourism; however, the literature remains fragmented, resulting in a lack of a cohesive and comprehensive framework [1]. Previous studies have found that tourists' risk perception has a high probability of impacting the image of tourist destinations and the intention to visit a destination [36], but little or no evidence is available on the role of religion values or related cultural backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Tourist safety at a destination is one of the most essential conditions that characterise the quality of experience [1]. The economic development of any country depends mainly on its security [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RQ4: What are the key personal and organizational factors that cause burnout among hotel employees? Data were collected from journals whose title refers to tourism and hospitality with an impact factor in the Web of Science (WoS) academic database, which includes a large number of social science and humanities journals and recognizes hospitality tourism as an independent academic category (Chen et al, 2023). This approach in the selection of journals was previously used in other papers (AnĎelić et al Data collection was conducted in September 2023, using the string (burnout OR -burning out‖ OR -burn out‖ OR -burns out‖ OR -burned out‖ OR -burnt out‖) AND (hotel OR hotels) for searching its appearance in title, abstract and keywords of the published papers using the advanced search options available on the websites of the publishers of the mentioned journals.…”
Section: Methodsmentioning
confidence: 99%
“…In the past, the perception of crowding was mainly a concern for psychology and geography scholars. However, in recent years, it has expanded to other fields, especially urban planning and environment, regional and urban planning, and environmental ecology [22]. The perception of crowding in urban micro spaces and micro public spaces is at the intersection of urban planning and design and psychology, and this study will have a specific contribution to urban planning and environmental psychology.…”
Section: Introductionmentioning
confidence: 97%